2015
DOI: 10.1073/pnas.1507309112
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 regulates mechanotransductive release of ATP from human RBCs

Abstract: Piezo proteins (Piezo1 and Piezo2) are recently identified mechanically activated cation channels in eukaryotic cells and associated with physiological responses to touch, pressure, and stretch. In particular, human RBCs express Piezo1 on their membranes, and mutations of Piezo1 have been linked to hereditary xerocytosis. To date, however, physiological functions of Piezo1 on normal RBCs remain poorly understood. Here, we show that Piezo1 regulates mechanotransductive release of ATP from human RBCs by controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
157
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(171 citation statements)
references
References 58 publications
9
157
2
Order By: Relevance
“…ATP is released from human erythrocytes in response to mechanical deformation or hypoxia. 107 Erythrocytes are not only O 2 carriers but also ATP release via pannexin 1 hemichannels has a direct role in regulation of vascular tone.…”
Section: Blood Cellsmentioning
confidence: 99%
“…ATP is released from human erythrocytes in response to mechanical deformation or hypoxia. 107 Erythrocytes are not only O 2 carriers but also ATP release via pannexin 1 hemichannels has a direct role in regulation of vascular tone.…”
Section: Blood Cellsmentioning
confidence: 99%
“…This protein has been identified in the RBC membrane, and in mice it has been shown to form a tetramer of about 1.2 million daltons; it is therefore the largest ion channel identified to date, and moreover it regulates mechanotransductive release of ATP from human RBCs. [40][41][42][43] The identified mutations are missense and mainly located in the highly conserved C-terminus of the protein, recently described to form the pore of the channel. 44 Several electrophysiology studies demonstrated that the mutations cause a gain-of-function phenotype with delayed inactivation of the channel, 38,39,45 sugUpdate of the red cell membrane disorders haematologica | 2016; 101 (11)gesting increased cation permeability leads to DHS erythrocyte dehydration.…”
Section: Anemias Due To Altered Permeability Of Rbc Membranementioning
confidence: 99%
“…Volume 126 Number 12 December 2016 studies using urothelial cells and red blood cells have also shown a PIEZO1-mediated mechanotransductive release of ATP, indicating that this is a cellular mechanism not restricted to endothelial cells (48,49). However, the process of PIEZO1-mediated ATP release from endothelial cells appears to involve additional mechanisms that still need to be fully explored.…”
mentioning
confidence: 99%